2016
DOI: 10.1126/science.aae0344
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequence assembly of the gorilla genome

Abstract: Accurate sequence and assembly of genomes is a critical first step for studies of genetic variation. We generated a high-quality assembly of the gorilla genome using single-molecule, real-time sequence technology and a string graph de novo assembly algorithm. The new assembly improves contiguity by two to three orders of magnitude with respect to previously released assemblies, recovering 87% of missing reference exons and incomplete gene models. Although regions of large, high-identity segmental duplications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
319
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(328 citation statements)
references
References 62 publications
(45 reference statements)
6
319
3
Order By: Relevance
“…Recent studies have highlighted the improvements of SMRT-only assemblies compared to Illumina-only assemblies [Bickhart et al, 2017], [Gordon et al, 2016], [Jiao et al, 2017], [Zhang et al, 2016], [Shi et al, 2016]. Here we found that both the pooled Illumina assembly (with mixed read length) and the PacBio SMRT-only assembly resulted in substantially improved assembly statistics compared to the two published hamster genome assemblies (Table 1), with an order of magnitude fewer scaffolds and 2–4x larger N50 values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted the improvements of SMRT-only assemblies compared to Illumina-only assemblies [Bickhart et al, 2017], [Gordon et al, 2016], [Jiao et al, 2017], [Zhang et al, 2016], [Shi et al, 2016]. Here we found that both the pooled Illumina assembly (with mixed read length) and the PacBio SMRT-only assembly resulted in substantially improved assembly statistics compared to the two published hamster genome assemblies (Table 1), with an order of magnitude fewer scaffolds and 2–4x larger N50 values.…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of such contiguous sequences is possible now with third generation sequencing technologies, such as Single Molecule Real Time (SMRT) sequencing technology [Eid et al, 2009], which provide mean read lengths that are more than an order of magnitude larger than earlier sequencing technologies. The reads can span repetitive elements, resulting in longer contigs and minimal gaps within scaffolds [Bickhart et al, 2017], [Jiao et al, 2017], [Gordon et al, 2016]. This enables the routine assembly of mammalian genomes approaching the current quality of the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is more expensive than short-read sequencing approaches, singlemolecule real-time (SMRT) sequencing improved the contiguity and repeat representation of mammalian (Pendleton et al 2015;Gordon et al 2016;Bickhart et al 2017) and diploid grass genomes (Zimin et al 2017). SMRT technologies are also being used to generate the complete sequence of transcripts, increasing the accuracy of splicing isoform definition (Abdel-Ghany et al 2016).…”
mentioning
confidence: 99%
“…This de novo assembly process is difficult for large and complex genomes (Istrail et al 2004;Chaisson et al 2015a;Gordon et al 2016;Steinberg et al 2016). A core challenge is the correct representation of highly similar sequences, which range in scale from single base repeats (homopolymers) to large complex events including segmental duplications (Bailey et al 2002).…”
mentioning
confidence: 99%